Augmenting the Oxidative Stability of Chicken Nuggets by incorporating cumin and Black cumin as natural preservatives - Muhammad Usman; Amna Sahar; Muhammad Haseeb Ahmad; Muhammad Issa Khan; Muhammad Faizan Afzal; Hafiz Ubaid Ur Rahman; Muhammad Azhar Ali; Waseem Khalid; Muhammad Zubair Khalid; Felix Kwashie Madilo (International Journal of Food Properties)
The present research investigated the effectiveness of cumin and black cumin extracts as natural antioxidants in uncooked chicken nuggets stored at refrigeration temperature (4°C) for 12 days and compared the results with a control treatment. Seven treatments were formulated, including a control group (Tc), T1 (0.5% cumin), T2 (1% cumin), T3 (1.5% cumin), T4 (0.5% black cumin), T5 (1% black cumin), and T6 (1.5% black cumin). The product was evaluated for several physicochemical parameters on days 0, 3, 6, 9, and 12 of storage. The data was analyzed using a two-way factorial design under a completely randomized (CRD) design. Results showed that both treatments and storage significantly impacted all physicochemical properties, including DPPH, TPC, pH, POV, and TBARS (p < 0.05). The values of TBARS significantly decreased with the increase in the concentration of cumin extract whereas TBARS increases during the storage period. Moreover, the interaction effect (Treatment*storage days) did not significantly affect any of the physicochemical parameters (p > 0.05). Sensory evaluation showed that T3 (1.5% cumin) was the most pleasant and preferred treatment. Conclusively, both cumin and black cumin have good antioxidant properties and can be used as natural antioxidants to increase the shelf life of food products.